Harnessing chloroplast SSRs to decipher genetic diversity in underutilized Allium species - Khade, Yogesh P.; Mainkar, Pawan; Chandanshive, Aniket; Rai, Krishna Madhav; Sinhasane, Shalaka R.; Jadhav, Manisha; Patil, Amol; Hembade, Vivekanand L.; Radhakrishna, Auji; More, Sanket J.; Khar, Anil; Bhandari, Hem Raj; et al. (Frontiers in Plant Science, 2025)
Alliums, including vital crops such as onion, garlic, chives, bunching onion, and leek, are globally prized for their culinary applications and medicinal attributes. However, their genetic improvement remains constrained by large genome size, high heterozygosity, and limited characterization of genetic resources. To bridge this gap, we developed chloroplast simple sequence repeat (cp-SSR) markers, which are particularly suitable for population genetics studies because of their maternal inheritance, low recombination rates, and high variability. Leveraging the chloroplast genome of Allium fistulosum, we identified 22 cp-SSR loci, with tetranucleotides being the most prevalent, followed by di-, tri-, and pentanucleotides. Screening 96 underutilized Allium accessions using polymorphic cp-SSR markers revealed 89.2% polymorphism, indicating substantial genetic diversity. The polymorphism information content (PIC) ranged from 0.00 to 0.66 (average 0.20), confirming the utility of these markers in diversity assessments. The population structure analysis revealed three distinct genetic clusters, whereas phylogenetic analysis categorized the accessions into six major clades, mirroring their evolutionary divergence. Fixation index (FST) analysis showed high genetic differentiation (mean FST = 0.6) among accessions. These findings underscore the significance of cp-SSRs in revealing genetic structure and diversity across underutilized Allium species. This work lays a crucial foundation for integrating chloroplast markers with nuclear genomic and omics tools to drive the development of resilient, high-value cultivars suited to future agricultural challenges.